Servomotor Assistance in the Improvement of Manual Wheelchair Mobility - Lahr, Gustavo Jose Giardini; Medola, Fausto Orsi [UNESP]; Sandnes, Frode Eika; Elui, Valeria Meirelles Carril; Fortulan, Carlos Alberto (IOS Press, 2017)
This study reports the development of a servo-controlled power-assisted wheelchair, designed to reduce the loads on the upper limbs while maintaining the drivability of a manual chair. It is presented the concept and implementation of an assisted propulsion system, focusing on the assistance controlling and the torque transmission.
Keywords: Mobility; Power-assistance; Wheelchairs